2021
DOI: 10.1017/s1474748021000396
|View full text |Cite
|
Sign up to set email alerts
|

The Zeroth -Stable Homotopy Sheaf of a Motivic Space

Abstract: We establish a kind of ‘degree $0$ Freudenthal ${\mathbb {G}_m}$ -suspension theorem’ in motivic homotopy theory. From this we deduce results about the conservativity of the $\mathbb P^1$ -stabilization functor. In order to establish these results, we show how to compute certain pullbacks in the cohomology of a strictly homotopy-invariant sheaf in terms of the Rost–Schmid complex. This establishes the main conjecture of [2], wh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
(69 reference statements)
0
2
0
Order By: Relevance
“…Again using that k has characteristic zero, Bachmann showed that the P 1suspension functor Q = Σ ∞ P 1 : H(k) * → SH(k) is conservative on A 1 -simply connected spaces which can be written as homotopy colimits of spaces X + ∧ G m with X ∈ Sm k [3,Theorem 1.3].…”
Section: Conservativity For the Motivic Stable Homotopy Categorymentioning
confidence: 99%
“…Again using that k has characteristic zero, Bachmann showed that the P 1suspension functor Q = Σ ∞ P 1 : H(k) * → SH(k) is conservative on A 1 -simply connected spaces which can be written as homotopy colimits of spaces X + ∧ G m with X ∈ Sm k [3,Theorem 1.3].…”
Section: Conservativity For the Motivic Stable Homotopy Categorymentioning
confidence: 99%
“…Note also that one can compose M k,Λ with the natural functors from the category of unstable motivic spaces and from the S 1 -stable motivic category SH S 1 (k) into SH Λ (k). Now, the recent Theorem 1.3 and Corollary 4.13 of [Bac20] give interesting conservativity statements for these functors (in the case Λ = Z; yet note that Proposition 1.2.5(4) gives an embedding of the corresponding category SH S 1 Λ (k) into SH S 1 (k)); thus one can describe even longer chains of (composable) conservative functors between various motivic categories. 2.…”
Section: Now Assume Thatmentioning
confidence: 99%